A modified 360° netting vein bionic structure for enhancing thermal properties of polymer/nanofiber/nanoparticle composite. (April 2021) - Sun, Yunna; Wu, Yongjin; Cai, Han; Luo, Jiangbo; Wang, Yan; Ding, Guifu
Abstract: A modified 360° netting vein bionic structure is proposed to improve the thermal properties of the composite. The influence of the fillers' distributed configuration on the composite thermal conductivity is analyzed with finite element method to optimize the filling ratio, filling angle and distributed form. With the purity and prewetting processes, the surface roughness and wetting property of SiC nano-fiber (SiCnf ) is improved. By adjusting the magnetic stirrer speed, the viscosity of Polyimide (PI) and filling ratio, a configuration of SiCnf in vertical direction is achieved for transferring heat and relieving stress effectively. Cu pillar serving as the main vein is fabricated with photography and electroplating. The thermal conductivity increases more than 40 times comparing with the pure PI. After mechanical loading test, fillers and Cu pillar are still reliable. Thus, this design has potential for transferring heat and relieving stress, just liking leaf vein system.